Analisis Voice of Customer Menggunakan SERVQUAL dan IPA Pada Startup Budidaya Lele Banyuwangi - Alief Lamsuna Pranoto; Endang Suprihatin; Muhammad Yusuf (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Samesta Kalipuro Banyuwangi's home catfish cultivation startup has experienced an increase in the number of customers after presenting clean catfish products. However, these improvements have not been followed by systematic measurement of customer needs and service quality. This research was conducted to identify customer needs, measure service quality, and determine improvement priorities using Voice of Customer (VoC), Service Quality (SERVQUAL), and Importance Performance Analysis (IPA). The study involved 22 customers as respondents. The results show that customers expect faster stock information and harvest schedules as well as increased product variety. SERVQUAL's analysis showed all attributes had negative gap values, with the largest gaps being in RS1 (-1.27), RS2 (-1.05), and E3 (-1.00). The IPA results show R1, RS1, and RS2 as service improvement priorities. In addition, the E3 attribute is also included in the improvement proposal because it has a large gap value. Proposed improvements include improving stock information, order service, product suitability, and developing product variations.